Radar and communication signal processing algorithm and implementation using OFDM based waveform - Liu, Changliang (My University, 2018)
With the development of radar systems, a platform that can support high estimation accuracy and multiple target tracking is required. OFDM is widely used in communication engineering due to the high spectrum efficiency. In this thesis, an algorithm of OFDM estimation method is developed based on the “RadCom” concept with data transmission and radar sensor. The algorithm is verified in hardware with 80 GHz carrier frequency. A novel approach on fractional step length estimation is demonstrated and tested for the improvement of radar estimation accuracy, improving the resolution for single target estimation beyond what is possible with the traditional integer step length method. Beside the OFDM-based “RadCom” system, this thesis presents a single-carrier radar system, which is developed using the tool suite DSP Builder and verified on an Arria V FPGA board.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science